Structural, morphological and photoluminescent properties of Nd-coated silicon nanostructures - Mefoued, Amine; Mahmoudi, Bedra; Benrekaa, Nasser; Tiour, Faiza; Menari, Hamid; Naitbouda, Abdelyamine; Manseri, Amar; Brik, Afaf; Mezghiche, Salah; Debbab, Moustafa (Opto-Electronics Review, 2023)
The structural, morphological and photoluminescent properties of thermally evaporated neodymium oxide (Nd2O3) thin films deposited onto nanostructured silicon (Si-ns) are reported. Si-ns embedded in silicon nitride (SiN) thin films are prepared by plasma-enhanced chemical vapour deposition (PECVD). SiN and Nd2O3 thin films uniformity and Si-ns formation are confirmed by atomic force microscopy (AFM) and scanning electron microscopy (SEM). The presence of neodymium (Nd), silicon (Si), oxygen (O), and phosphorus (P) is investigated by energy-dispersive spectroscopy (EDS) and secondary ion mass spectrometry (SIMS). Post-annealing SIMS profile indicates an improvement of the homogeneity of activated P distribution in Si bulk. The X-ray diffraction (XRD) combined with Raman spectroscopy and Fourier-transform infrared spectroscopy (FTIR) have been employed to determine amorphous silicon (a-Si), crystalline silicon (c-Si), Nd2O3 and SiN phases present in the Nd2O3-SiN bilayers with their corresponding chemical bonds. After annealing, a Raman shift toward lower wavenumbers is recorded for the Si peak. XPS data reveal the formation of Nd2O3 thin films with Nd-O bonding incorporating trivalent Nd ions (Nd3+). Strong room-temperature photoluminescence is recorded in the visible light range from the Si-ns. Nd-related photoluminescent emission in the near infrared (NIR) range is observed at wavelengths of 1025–1031 nm and 1083 nm, and hence is expected to improve light harvesting of Si-based photovoltaic devices.